Physiological Responses to Linear and Nonlinear Soccer-specific Match Simulations and Their Effects on Lower-Limb Muscle Fatigue. Issue 11 (November 2020) - Uddin, Nasir; Jeffries, Owen; Read, Paul; Howe, Louis; Patterson, Stephen; Waldron, Mark
Abstract : Abstract: Uddin, N, Jeffries, O, Read, P, Howe, L, Patterson, S, and Waldron, M. Physiological responses to linear and nonlinear soccer-specific match simulations and their effects on lower-limb muscle fatigue. J Strength Cond Res 34(11): 3232–3240, 2020—The aims of this study were to: (a) investigate the effects of linear and nonlinear soccer simulations on lower-limb muscle function and physiological responses and (b) evaluate the relationship between match-running demands and changes in lower-limb muscle function. In a repeated-measures cross-over design, 8 participants completed either a linear or nonlinear adapted Loughborough Intermittent Shuttle Test (LIST) on 2 occasions. The movement of players was tracked with a global positioning system, while lower-limb muscle function tests and physiological measurements were performed before and every 15 minutes during the simulation. There were no differences in distance covered, yet high-speed running ( p = 0.007), accelerations ( p = 0.008), and decelerations ( p = 0.015) were higher in the linear LIST. Mean heart rate ( p = 0.001) and ratings of perceived exertion ( p = 0.013) were higher in the nonlinear LIST. Peak landing forces ( p = 0.017) and jump height ( p = 0.001) were reduced between baseline and 90 minutes but were not different between conditions. Changes in peak landing forces from baseline to half-time ( r = −0.57, n = 16, p = 0.022) and full-time ( r = −0.58, n = 16, p = 0.019) were related to high-speed running. Hamstring force was unaffected by time ( p = 0.448) but was reduced in the linear LIST ( p = 0.044). Protocols posing different external and internal demands elicited similar levels of fatigue across simulations. Hamstring function was not an effective indicator of fatigue, but our results highlight the greater demands placed on this muscle group when higher-speed running is performed.